Gastric Bypass Surgery Enhances Glucagon-Like Peptide 1–Stimulated Postprandial Insulin Secretion in Humans - Salehi, Marzieh; Prigeon, Ronald L.; D’Alessio, David A. (Diabetes (New York, N.Y.), 2011)
Gastric bypass (GB) surgery is associated with postprandial hyperinsulinemia, and this effect is accentuated in postsurgical patients who develop recurrent hypoglycemia. Plasma levels of the incretin glucagon-like peptide 1 (GLP-1) are dramatically increased after GB, suggesting that its action contributes to alteration in postprandial glucose regulation. The aim of this study was to establish the role of GLP-1 on insulin secretion in patients with GB. Twelve asymptomatic individuals with previous GB (Asym-GB), 10 matched healthy nonoperated control subjects, and 12 patients with recurrent hypoglycemia after GB (Hypo-GB) had pre- and postprandial hormone levels and insulin secretion rates (ISR) measured during a hyperglycemic clamp with either GLP-1 receptor blockade with exendin-(9-39) or saline. Blocking the action of GLP-1 suppressed postprandial ISR to a larger extent in Asym-GB individuals versus control subjects (33 ± 4 vs.16 ± 5%; P = 0.04). In Hypo-GB patients, GLP-1 accounted for 43 ± 4% of postprandial ISR, which was not significantly higher than that in Asym-GB subjects (P = 0.20). Glucagon was suppressed similarly by hyperglycemia in all groups but rose significantly after the meal in surgical individuals but remained suppressed in nonsurgical subjects. GLP-1 receptor blockade increased postprandial glucagon in both surgical groups. Increased GLP-1-stimulated insulin secretion contributes significantly to hyperinsulinism in GB subjects. However, the exaggerated effect of GLP-1 on postprandial insulin secretion in surgical subjects is not significantly different in those with and without recurrent hypoglycemia.